PELAKSANAAN PROGRAM SANITASI PERDESAAN PADAT KARYA DI DESA TANJUNG AIR HITAM KECAMATAN KERUMUTAN KABUPATEN PELALAWAN TAHUN 2021 - Putra, Ari Adia; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The labor-intensive rural sanitation program has provided access or opportunities for workers, especially craftsmen in the villages, in the sense that this program aims to provide employment opportunities for craftsmen who currently or do not have work so that with the existence of government programs that require craftsmen they can provide income. as well as improving the economic level of village communities. In this way, it can help the economy of the poor. This research aims to analyze the community's response regarding the implementation of a labor-intensive rural sanitation program in Tanjung Air Hitam Village, Kerumutan District, Pelalawan Regency in 2021. The method in this research uses a descriptive quantitative approach. Data sources consist of primary data and secondary data collected through questionnaires, interviews and documentation. The results of this research indicate that the implementation of the sanitation program in Tanjung Air Hitam Village was carried out by craftsmen from outside the village, giving rise to opposition within the village community. This has been proven based on research results using questionnaires as a measuring tool for responses from respondents/the public. And not all poor people receive the Tanjung Air Hitam Village Sanitation Program. This is proven by the number of sanitation facilities intended for poor people, which amounted to 79 people, but only 52 people were able to accept it, while the remaining 27 people or other poor people who were promised a number of jobs from this program were in fact not involved as artisan workers. This has caused disappointment for the people of Tanjung Air Hitam Village. Keywords: Policy, Implementation, Sanitation Program